Managing uncertainty and references to time in prognostic conversations with family members at the end of life: A conversation analytic study. (July 2020) - Anderson, Rebecca J; Stone, Patrick C; Low, Joseph T S; Bloch, Steven
Background: When patients are likely to die in the coming hours or days, families often want prognostic information. Prognostic uncertainty and a lack of end-of-life communication training make these conversations challenging. Aim: The objective of this study is to understand how clinicians and the relatives/friends of patients at the very end of life manage uncertainty and reference time in prognostic conversations. Design: Conversation analysis of audio-recorded conversations between clinicians and the relatives/friends of hospice inpatients. Setting/participants: Experienced palliative care clinicians and relatives/friends of imminently dying hospice inpatients. Twenty-three recorded conversations involved prognostic talk and were included in the analysis. Results: Requests for prognostic information were initiated by families in the majority of conversations. Clinicians responded using categorical time references such as 'days', allowing the provision of prognostic estimates without giving a precise time. Explicit terms such as 'dying' were rare during prognostic discussions. Instead, references to time were understood as relating to prognosis. Relatives displayed their awareness of prognostic uncertainty when requesting prognostic information, providing clinicians with 'permission' to be uncertain. In response, clinicians often stated their uncertainty explicitly, but presented evidence for their prognostic estimates, based on changes to the patient's function previously discussed with the family. Conclusion: Prognostic uncertainty was managed collaboratively by clinicians and families. Clinicians were able to provide prognostic estimates while being honest about the related uncertainty, in part because relatives displayed their awareness of uncertainty within their requests. The conversation analytic method identified contributions of both clinicians and families, and identified strategies based on real interactions, which could inform communication training.